2019
DOI: 10.1128/jb.00757-18
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of the Streptococcus agalactiae Sht-Family Proteins in Zinc Acquisition and Complement Evasion

Abstract: Streptococcus agalactiae is not only part of the human intestinal and urogenital microbiota but is also a leading cause of septicemia and meningitis in neonates. Its ability to cause disease depends upon the acquisition of nutrients from its environment, including the transition metal ion zinc. The primary zinc acquisition system of the pathogen is the Adc/Lmb ABC permease, which is essential for viability in zinc-restricted environments. Here, we show that in addition to the AdcCB transporter and the three zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 43 publications
(64 reference statements)
2
28
0
Order By: Relevance
“…Fig 1A). To confirm what has been previously described for GBS in zinc-limited chemically defined media (38,39), we observed that mutants lacking individual zinc-binding proteins exhibited similar calprotectin sensitivity as the WT GBS strain, while growth of a triple ΔadcAΔadcAIIΔlmb mutant was reduced (Supplemental Fig 1B). This is consistent with previous results that suggest functional redundancy exists between zinc-binding proteins.…”
Section: Global Impact Of Calprotectin On Gbs Fitnesssupporting
confidence: 82%
See 2 more Smart Citations
“…Fig 1A). To confirm what has been previously described for GBS in zinc-limited chemically defined media (38,39), we observed that mutants lacking individual zinc-binding proteins exhibited similar calprotectin sensitivity as the WT GBS strain, while growth of a triple ΔadcAΔadcAIIΔlmb mutant was reduced (Supplemental Fig 1B). This is consistent with previous results that suggest functional redundancy exists between zinc-binding proteins.…”
Section: Global Impact Of Calprotectin On Gbs Fitnesssupporting
confidence: 82%
“…The GBS zinc uptake machinery is encoded by four distinct operons and is under the regulation of the zinc-dependent AdcR repressor (38). AdcR is involved in maintaining intracellular zinc homeostasis, and has been shown to be important for growth in zinc-limiting conditions (38,39). This system is also significantly upregulated during GBS murine vaginal colonization and following incubation with human blood (71,72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of Hnt1 decreases markedly during deficiency (Wang et al, ). Moreover, members of the broader histidine triad superfamily have been implicated in zinc homeostasis suggesting a possible role for Hnt1 in these processes (Moulin et al, ). Future experiments will test these models to examine how HNT1 regulation impacts gene expression and cell physiology during zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The fraction of intensity of each band relative to the total intensity of the three bands in each grouping is plotted. p values were less than .001 for when comparing the zinc-deficient samples to their control; no statistically significant differences were observed among the zincreplete samples Moreover, members of the broader histidine triad superfamily have been implicated in zinc homeostasis suggesting a possible role for Hnt1 in these processes (Moulin et al, 2019). Future experiments will test these models to examine how HNT1 regulation impacts gene expression and cell physiology during zinc deficiency.…”
Section: F I G U R Ementioning
confidence: 96%